TINDAK TUTUR HAKIM BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NO. 49 TAHUN 2009 TENTANG PERADILAN UMUM - Syahfitri Purnama (Universitas Indraprasta PGRI, 2015)
Speech act is a human act that is done in nearly all activities. According to Austin, speech acts consist of the locutionary acts are acts of speaking which serves as a transfer medium to the listener, illocutionary acts are acts done in speaking which are arranged in a speech to inform something under the control of the speaker, and perlocutionary acts which is a consequences or by product of speaking. The paper is titled